Altered functional connectivity of cerebellar networks in first-episode schizophrenia - Feng, Sitong; Zheng, Sisi; Zou, Haoming; Dong, Linrui; Zhu, Hong; Liu, Shanshan; Wang, Dan; Ning, Yanzhe; Jia, Hongxiao (Frontiers in Cellular Neuroscience, 2022)
Abnormalities of the cerebellum have been displayed to be a manifestation of schizophrenia (SCH) which is a detrimental psychiatry disorder. It has been recognized that the cerebellum contributes to motor function, sensorimotor function, cognition, and other brain functions in association with the cerebral functions. Multiple studies have observed that abnormal alterations in cerebro-cerebellar functional connectivity (FC) were shown in SCH patients. However, FC of cerebellar networks in SCH remains unclear. In this study, we explored FC of cerebellar networks of 45 first-episode SCH patients and 45 healthy control subjects by using a defined Yeo 17 network parcellation system. Furthermore, we performed a correlation analysis of between cerebellar networks’ FC and positive and negative symptoms in first-episode SCH patients. Finally, we established the classification model to provide relatively suitable features of first-episode SCH patients concerning the cerebellar networks. We found lower between-network FCs between 14 distinct cerebellar network pairs in first-episode SCH patients, compared to the healthy controls. Significantly, the between-network FC in N2-N15 was positively associated with positive symptom severity, meanwhile N4-N15 was negatively associated with negative symptom severity. Besides, our results revealed a satisfactory classification accuracy (79%) of these decreased between-network FCs of cerebellar networks for correctly identifying first-episode SCH patients. Conclusively, between-network abnormalities in the cerebellum are closely related with positive and negative symptoms of first-episode SCH patients. And the classification results suggest the cerebellar networks can be a potential target for further elucidating the underlying mechanisms in first-episode SCH.